ANALISIS MARJIN PEMASARAN DAGING SAPI DI PASAR-PASAR TRADISIONAL KOTA MEDAN - Edi Suherman (Universitas Sumatera Utara, 2015)
ABSTRACT This study aimed to determine the systematic distribution of beef from the producer until to consumer. The experiment was conducted at feedlot, at slaughter house and traditional market in Medan on April 2014 to May 2014. The research used survey method with 7 traditional markets and 35 respondents. Primary data were obtained from the beef sellers in the traditional marketin Medan, while the secondary data obtained from various relevant agencies, such as the central institution of statistics and the slaughter house Mabar and slaughter TaniAsli. The parameters studied were marketing margin of the beef. There are two types of marketing channels contained in the marketing process of beef from the producer until to consumer.The first channel was producer - wholesaler - retailer - consumer and the second channel was producer - agent – wholesaler - consumer. Marketing margin at the wholesalers were Rp. 3.311 million/head and at the retailers were Rp. 1.992 million/head. The conclusion is the shorter market chain have higher marketing margin on wholesaler. This suggests that the best marketing channel for beef seller was the second channel that is: producer - agent– wholesaler – consumer. Keywords :Marketing Margin, Beef, Traditional Markets in Medan